Evolutional trends in the management of tracheal and bronchial injuries - Madden, Brendan Patrick (Journal of Thoracic Disease, 2017)
Tracheal and Bronchial injuries are potentially life threatening complications which require urgent diagnosis and therapeutic intervention. They typically occur in association with blunt and penetrating chest trauma although they are increasingly being encountered in patients following endobronchial intervention and percutaneous tracheostomy insertion. Their precise incidence is unknown. Presenting features include dyspnoea, stridor, respiratory and haemodynamic compromise, haemoptysis, surgical emphysema, pneumothorax and persistent significant airleak. There may be other additional injuries to consider in trauma patients with large airway injury. Familiarity with the diagnosis and management of large airway injuries is important for medical teams engaged in emergency medicine, thoracic surgery and medicine, anaesthesia and intensive care. Although early surgical intervention is the mainstay of treatment, endobronchial manoeuvres to seal defects are receiving increasing attention particularly for patients with medical co-morbidities which may contraindicate formal surgery or transfer or where local surgical expertise is not available.